Newborn organ weight and spontaneous hypertension: recombinant inbred strain study - Dobesová, Z; Zicha, J; Kunes, J (Clinical and experimental hypertension (New York, N.Y., 1997)
Heart and kidney weight of newborn rats was studied in two progenitor strains (Brown Norway-BN, and spontaneously hypertensive rats-SHR) and in 31 recombinant inbred (RI) strains developed by inbreeding of F2 cross derived from these two progenitors. The relative weight of both organs was significantly higher in SHR newborns than in BN ones. No differences in relative DNA, protein and water contents were detected in hearts from SHR and BN newborns. On the other hand, in SHR kidneys there was lower DNA and protein content accompanied by a higher water content. This suggested that kidneys of SHR babies had less cells with higher water content. The average body weight of newborns in individual RI strains was continuously distributed between both progenitor strains but more RI strains resembled values of SHR newborns. The opposite was true for relative heart and kidney weights where the predominant influence of BN genes was visible. Moreover, there was an important difference between two reciprocal crosses of RI strains because the relative heart weight was clustered around SHR values only in BxH but not in HxB cross. This was, however, not observed for body weight and relative kidney weight. No significant correlation between blood pressure of adult males and body weight or relative organ weights of newborns of RI strains was found. On the other hand, relative heart and kidney weights of newborns correlated positively with the same parameters in adult males of respective RI strains. Additionally, relative heart weight of newborns was related positively to blood pressure of their mothers only in HxB cross that was derived from SHR females. It can be concluded that 1) kidney enlargement observed in newborn SHR is due to increased water content, 2) organ weight in adulthood can be predicted from newborn organ weight, and 3) heart weight in newborns correlated significantly with maternal blood pressure in HxB but not in BxH cross. It should be noted that the relationship between heart and/or kidney weight at birth and blood pressure in adulthood has not been proven to be significant (at p < 0.05 level) in Prague set of recombinant inbred strains.
Keywords: hypertenze; Male; potkani inbrední SHR; Organ Size; Animals, Newborn; velikost orgánu; stárnutí; Diastole; Animals; diastola; potkani inbrední BN; krevní tlak; Myocardium; mužské pohlaví; Female; novorozená zvířata; krysa rodu Rattus; Kidney; Blood Pressure; Aging; Reference Values; Rats; myokard; Rats, Inbred SHR; ženské pohlaví; rekombinace genetická; pohlavní dimorfismus; Sex Characteristics; Rats, Inbred BN; DNA; zvířata; ledviny; Recombination, Genetic; Hypertension; referenční hodnoty